My Autism Buddy (MAB) / Zuraidah Sipon … [et al.] - Sipon, Zuraidah; Mohamed Yousop, Nur Liyana; Ramdhan, Nur'asyiqin; Roslan, Shashazrina; Mohd Hasan Abdullah, Norhasniza; Ahmad, Zuraidah (Division of Research and Industry Linkages, 2017)
According to the Americans with Disabilities Act of 1990 (ADA), “A person is considered to have a disability if he or she has difficulty performing certain functions (seeing, hearing, talking, walking, climbing stairs and lifting and carrying), or has difficulty performing activities of daily living, or has difficulty with certain social roles (doing school work for children, working at a job and around the house for adults)." Autism spectrum disorder (ASD) is the name of a group of developmental disorders. ASD includes a wide range, "a spectrum,” of symptoms, skills and levels of disability. Unfortunately, the very fact that these symptoms are invisible, can lead to misunderstandings, false perceptions and judgments. Autistic people often do not ‘look’ disabled. Some parents of autistic children say that other people simply think their child is naughty, while adults find that they are misunderstood. The process of educating the public is essential to be done especially at school level to change the current misunderstandings, false perceptions and judgments toward the autistics. Due to that circumstance, our aim is to develop a new environment and practice at school where the school community are aware, educated and always ready to engage themselves with the autistics. Promoting the usage of wristband among the autistic buddies at school will be able to set a new way of how the normal kids see their so called ‘special friends'.